Religion in the Polish Geopolitical Codes in the Period 1990-2017 on the Example of the Information of the Ministers of Foreign Affairs on the Foreign Policy of the Republic of Poland - Macała, Jarosław (Przegla̜d religioznawczy, 2018)
In present geopolitics, mainly in western publications, religion is not an important factor. Particularly, that religion is hardly ever the only influencing on geopolitical processes factor, but it correlates with many different variables which are hard influences to examine and to measure. From here, there is a lot more scientific research over relationships between geopolitics and the culture. One of the key indicators of a country's position in global affairs and its foreign policy trends is the geopolitical code. Geopolitical code is defined as the operating code of a government's foreign policy that evaluates places beyond its boundaries. The religion played a minor role in Polish geopolitical codes, analyzed mainly in context of membership of Poland in the western civilization circle. Poles' Catholicism emphasized it. Religion, mainly Islam was treated as a threat in adapted from USA hegemonic geopolitical code of war on terror.